2020
DOI: 10.1111/ppa.13175
|View full text |Cite
|
Sign up to set email alerts
|

Induction of systemic resistance to Agrobacterium tumefaciens by endophytic bacteria in grapevine

Abstract: Crown gall disease of grapevine, caused by Agrobacterium tumefaciens, often results in severe economic loss to grape production worldwide. This study demonstrated the ability of the endophytic bacteria Pseudomonas sp. Sn48 and Pantoea sp. Sa14 isolated from domesticated and wild grapevines to induce resistance in both above‐ and belowground tissues of grapevines infected with A. tumefaciens. Our results provide evidence that both strains can colonize roots and/or shoots. We showed that the strains Pseudomonas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…While acibenzolar-s-methyl treatment was able to overexpress CaDEF1 gene in accordance with Zhang et al, 32 where P. capsici induced an overexpression of the defensin gene in pepper 24 h after the inoculation. Moreover, compost water suspension treated plants overexpressed CaPBR1 gene at T24 in accordance with Asghari et al, 40 and Esmail et al, 41 who demonstrated overexpression of the target gene 24 h after inoculation respectively in: grapevine plants against Agrobacterium tumefaciens and in Triticum aestivum plants primed with diverse Trichoderma strains against Puccinia graminis f. sp. tritici.…”
Section: Discussionsupporting
confidence: 80%
“…While acibenzolar-s-methyl treatment was able to overexpress CaDEF1 gene in accordance with Zhang et al, 32 where P. capsici induced an overexpression of the defensin gene in pepper 24 h after the inoculation. Moreover, compost water suspension treated plants overexpressed CaPBR1 gene at T24 in accordance with Asghari et al, 40 and Esmail et al, 41 who demonstrated overexpression of the target gene 24 h after inoculation respectively in: grapevine plants against Agrobacterium tumefaciens and in Triticum aestivum plants primed with diverse Trichoderma strains against Puccinia graminis f. sp. tritici.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, some microbes can induce plant defenses. Asghari et al (2020) demonstrated that Pseudomonas sp. Sn48 and Pantoea sp.…”
Section: Introductionmentioning
confidence: 99%
“…Crown gall disease was identified long ago as a bacterial plant disease [1], and its pathogenic bacterium is Agrobacterium tumefaciens, which mainly infects dicots. This disease often results in severe economic losses to the production of cherry and other fruit trees [2][3][4]. Crown gall disease starts with the attachment of A. tumefaciens to plant cell.…”
Section: Introductionmentioning
confidence: 99%